1995
DOI: 10.1161/01.str.26.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen in Patients With Moyamoya Disease

Abstract: These findings suggest that there may be a genetic predisposition for moyamoya disease and that host factors may play a role in the development of intimal thickening in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 20 publications
1
26
3
Order By: Relevance
“…The results showed a statistically significantly increase in the frequency of the HLA-B35 allele in MMD patients compared with healthy controls (phenotype frequency: 32.1% in patients versus 10.1% in controls; relative risk¼4.2; Po0.008). Previous findings 25,37 on HLA-B51, DRB1*0405, DQB1*0502 and DQB1*0401 in a Japanese cohort could not be replicated in this study.…”
Section: Acta2contrasting
confidence: 95%
See 1 more Smart Citation
“…The results showed a statistically significantly increase in the frequency of the HLA-B35 allele in MMD patients compared with healthy controls (phenotype frequency: 32.1% in patients versus 10.1% in controls; relative risk¼4.2; Po0.008). Previous findings 25,37 on HLA-B51, DRB1*0405, DQB1*0502 and DQB1*0401 in a Japanese cohort could not be replicated in this study.…”
Section: Acta2contrasting
confidence: 95%
“…Further examination of 22 microsatellite markers from the 9-cM region between D17S785 and D17S836 showed LOD scores up to 4.58 in multipoint linkage studies, making an association between MMD and 17q25 likely. To confirm previous results 25,37 for an association between HLA and MMD, Han et al 38 phenotyped and genotyped different HLA alleles in a Korean cohort of 28 Moyamoya patients and 198 unrelated healthy controls. HLA class I typing consisted of serological typing of HLA-A and -B, where positive results on HLA-B35 were confirmed by amplification refractory modification system-PCR.…”
Section: Acta2mentioning
confidence: 60%
“…Previous reports have shown associations between the disease and either 1) Aw24, Bw46, or Bw54 antigens in 18 patients (Kitahara et al, 1982) and 2) B51, B67, DR1 or Cwl antigens in 32 patients (Aoyagi et al, 1995). In contrast to these reports, no such counterparts of these alleles were seen in this present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The responsible gene of neurofibromatosis is located on chromosome 17q or 22q. A complementation group of Fanconi anemia is related to chromosome 9q, while Down syndrome is known to demonstrate 21-trisomy; and 4) Previous serological typing of HLA in moyamoya disease revealed associations between the disease and A w24, Bw46 and Bw54 antigens in 18 patients (Kitahara et alo, 1982), or B51, B67, DR1 and Cwl antigens in 32 patients (Aoyagi et al, 1995)_ The purpose of this study is, thus, to elucidate the genetic factors that may control the susceptibility to moyamoya disease by performing DNA typing of HLA genes in a large number of unrelated Japanese patients with this disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been also reported that there is a significant association of the human leukocyte antigen B51 in patients with this disease. [2] These findings suggest that some genetic factors possibly take part in the pathogenesis. However, the paucity of clinical materials for investigations has not allowed a direct determination of the pathogenesis of moyamoya disease.…”
Section: Introduction By Haruhiko Kikuchi MD and Susumu Miyamoto mentioning
confidence: 95%